2000
DOI: 10.1177/014572170002600610
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Variables Associated With Inaccurate Self-Monitoring of Blood Glucose: Proposed Guidelines to Improve Accuracy

Abstract: As a result of the study, guidelines were subsequently developed to evaluate meter accuracy in an outpatient setting. Further effort is needed to establish standards for evaluating SMBG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 8 publications
1
74
0
4
Order By: Relevance
“…However, the potential for operator error still exists and remains the largest source of error (up to 91-97%) overall (46, [62][63][64]. Sources of error such as differences between lots of test strips (up to 14.5 mg/ dl) in some (28,65) but not all (19,31) studies may be unrecognized.…”
Section: Operator Errormentioning
confidence: 99%
“…However, the potential for operator error still exists and remains the largest source of error (up to 91-97%) overall (46, [62][63][64]. Sources of error such as differences between lots of test strips (up to 14.5 mg/ dl) in some (28,65) but not all (19,31) studies may be unrecognized.…”
Section: Operator Errormentioning
confidence: 99%
“…Patient education has the potential to improve accuracy. 19,20 In our study, subjects were able to correctly use the system, even without any further training than the user manual. Nearly all responses to the user acceptance questionnaire indicated that the meter was easy to learn and easy to use (98.7% neutral or better response; 96.6% CI LL).…”
Section: Discussionmentioning
confidence: 67%
“…8,9 Therefore, accurate testing methods are important to form a basis for accurate adjustment of treatment. However, research on the impact of accurate vs inaccurate procedure for BG testing is limited.…”
Section: Discussionmentioning
confidence: 99%